2018
DOI: 10.18632/oncotarget.24455
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MET gene amplification and TP53 mutation with PD-L1 expression in non-small cell lung cancer

Abstract: BackgroundThe role of MET amplification in lung cancer, particularly in relation to checkpoint inhibition and EGFR WT, has not been fully explored. In this study, we correlated PD-L1 expression with MET amplification and EGFR, KRAS, or TP53 mutation in primary lung cancer.MethodsIn this retrospective study, tissue collected from 471 various tumors, including 397 lung cancers, was tested for MET amplification by FISH with a MET/centromere probe. PD-L1 expression was evaluated using clone SP142 and standard immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 50 publications
7
32
1
Order By: Relevance
“…In the present study, high MET expression was associated with high p-GSK3B (Y56), low PDL1 expression, and high granzyme B levels in clinical HCC samples ( Figure 5A and B) with detailed mechanisms ( Figure 5C). Although several studies showed inconsistent correlation between MET amplification and PDL1 expression, 36,37 it is not yet clear whether and how MET directly regulates PDL1 expression in different cell types. Although MET positively correlates with PDL1 in non-small cell lung cancer, 36 the correlation in clear cell renal cell carcinoma seems to be inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, high MET expression was associated with high p-GSK3B (Y56), low PDL1 expression, and high granzyme B levels in clinical HCC samples ( Figure 5A and B) with detailed mechanisms ( Figure 5C). Although several studies showed inconsistent correlation between MET amplification and PDL1 expression, 36,37 it is not yet clear whether and how MET directly regulates PDL1 expression in different cell types. Although MET positively correlates with PDL1 in non-small cell lung cancer, 36 the correlation in clear cell renal cell carcinoma seems to be inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies showed inconsistent correlation between MET amplification and PDL1 expression, 36,37 it is not yet clear whether and how MET directly regulates PDL1 expression in different cell types. Although MET positively correlates with PDL1 in non-small cell lung cancer, 36 the correlation in clear cell renal cell carcinoma seems to be inconsistent. 37 To validate this, we compared the correlation between p-MET and PDL1 in several lung cancer and HCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies 25,26 reported that PD-L1 expression in NSCLCs is inversely correlated with EGFR mutation and positively correlated with TP53 mutation and MET amplification. The current results also showed that PD-L1 is highly expressed in NSCLC patients with MET exon 14 skipping (69.2% vs 17.3%, P < 0.01), and significantly lower in patients with EGFR mutant cohort (9.3% vs 26.9%, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 expression occurs more frequently with MET activation in NSCLC (25), suggesting that besides its well-characterized direct anti-tumor effects inhibition of c-MET signaling may act indirectly to alleviate immunosuppression. Increasing PD-L1 expression correlated positively with MET gene amplification in 389 NSCLC samples (26). A separate study of 155 resected NSCLC tumor samples found MET activation was associated with PD-L1 expression and demonstrated that in NSCLC cell lines c-MET signaling directly induces PD-L1 expression (25).…”
Section: C-met and Immune Evasionmentioning
confidence: 95%